Struktur Kepribadian Manusia Perspektif Pendidikan Islam - Nuruzzahri, Nuruzzahri (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2024)
Human personality embodies both animalistic and angelic traits, often leading to an internal struggle between these two aspects. At times, individuals are driven by their bodily desires and instincts, while at other times, they are guided by their spiritual needs. In the Qur'an, human personality is referred to as human potential or fitrah, a divine endowment from the Creator. This potential can incline individuals toward goodness or wrongdoing, depending on whether they follow the whispers of desire (nafs) or the guidance of intellect (‘aql). The Qur'an categorizes human personality into three main types: Mukmin (believers), Kafir (disbelievers), and Munafikun (hypocrites). This study explores the structural composition of human personality from an Islamic perspective, analyzing how these classifications reflect the dynamic interplay between spiritual and material inclinations. By examining Qur'anic discourse, the study highlights the underlying principles that shape human behavior and ethical choices. The findings contribute to a deeper understanding of Islamic psychology, emphasizing the role of divine guidance in personal development and moral decision-making.